The economic development of Japan : - Lockwood, William W. (Princeton, 1968)
This volume was begun several years ago as a modest inquiry into the international aspects of Japan's economic growth in modern times: the importance to Japan of the international order which her militarists had done so much to destroy, and which would have to be recreated in its essentials if she were again to prosper; to challenge a notion prevalent in books about Japan.